Medicinal Plants Used for Eye Conditions in Mexico-A Review - Anuar Salazar-Gómez; Amabile A. Velo-Silvestre; Angel Josabad Alonso-Castro; Luis Fernando Hernández-Zimbrón (MDPI AG, 2023)
Medicinal plants have been historically significant for treating common human diseases in Mexico. Although some ethnobotanical research exists, limited ethnomedicinal data has documented medicinal plants employed for eye health. This review focuses on ethnomedicinal information and preclinical and clinical studies regarding medicinal plants used in Mexico for treating symptoms associated with eye conditions. An electronic database search was conducted by consulting scientific articles, books about Mexican herbal medicine, and academic theses. This work recorded 69 plant species belonging to 26 plant families, especially plants from the Crassulaceae family, which are used as remedies for irritation and infections in the eye. Eight of these medicinal plants have been the subject of preclinical studies using ocular models, and one medicinal plant has been tested in clinical trials. The evidence of pharmacological effects indicates the promising therapeutic potential of these medicinal plants for developing new treatments for eye conditions. However, toxicological studies are necessary to ensure safe application to the eye, particularly as traditional medicine continues to be relied upon worldwide. In addition, this review highlights the need to perform ethnobotanical and phytochemical studies in Mexico regarding the medicinal flora used as remedies for eye conditions.